Molecular and metabolomic characterization of hiPSC-derived cardiac fibroblasts transitioning to myofibroblasts - Nagalingam, Raghu Sundaresan; Jayousi, Farah; Hamledari, Homa; Dababneh, Saif; Hosseini, Dina; Lindsay, Chloe; Klein Geltink, Ramon; Lange, Philipp F.; Dixon, Ian Michael; Rose, Robert Alan; Czubryt, Michael Paul; Tibbits, Glen Findlay (Frontiers in Cell and Developmental Biology, 2024)
BackgroundMechanical stress and pathological signaling trigger the activation of fibroblasts to myofibroblasts, which impacts extracellular matrix composition, disrupts normal wound healing, and can generate deleterious fibrosis. Myocardial fibrosis independently promotes cardiac arrhythmias, sudden cardiac arrest, and contributes to the severity of heart failure. Fibrosis can also alter cell-to-cell communication and increase myocardial stiffness which eventually may lead to lusitropic and inotropic cardiac dysfunction. Human induced pluripotent stem cell derived cardiac fibroblasts (hiPSC-CFs) have the potential to enhance clinical relevance in precision disease modeling by facilitating the study of patient-specific phenotypes. However, it is unclear whether hiPSC-CFs can be activated to become myofibroblasts akin to primary cells, and the key signaling mechanisms in this process remain unidentified.ObjectiveWe aim to explore the notable changes in fibroblast phenotype upon passage-mediated activation of hiPSC-CFs with increased mitochondrial metabolism, like primary cardiac fibroblasts.MethodsWe activated the hiPSC-CFs with serial passaging from passage 0 to 3 (P0 to P3) and treatment of P0 with TGFβ1.ResultsPassage-mediated activation of hiPSC-CFs was associated with a gradual induction of genes to initiate the activation of these cells to myofibroblasts, including collagen, periostin, fibronectin, and collagen fiber processing enzymes with concomitant downregulation of cellular proliferation markers. Most importantly, canonical TGFβ1 and Hippo signaling component genes including TAZ were influenced by passaging hiPSC-CFs. Seahorse assay revealed that passaging and TGFβ1 treatment increased mitochondrial respiration, consistent with fibroblast activation requiring increased energy production, whereas treatment with the glutaminolysis inhibitor BPTES completely attenuated this process.ConclusionOur study highlights that the hiPSC-CF passaging enhanced fibroblast activation, activated fibrotic signaling pathways, and enhanced mitochondrial metabolism approximating what has been reported in primary cardiac fibroblasts. Thus, hiPSC-CFs may provide an accurate in vitro preclinical model for the cardiac fibrotic condition, which may facilitate the identification of putative anti-fibrotic therapies, including patient-specific approaches.